Drivers and barriers to the choice of production systems among smallholder pig farmers: Evidence from Northern Uganda - Caleb Ibukunoluwa Adewale; Elly Kurobuza Ndyomugyenyi; Basil Mugonola (Heliyon)
Pork consumption has risen significantly in many emerging nations, prompting diverse pig production systems. This study explored the drivers and barriers to the choices of pig production systems and the challenges confronting pig farmers in Northern Uganda. Data were collected from 240 pig farmers using a structured questionnaire and analyzed using multinomial logit regression. Results revealed that 38.8 % of the pig farmers practiced the farrow-to-weaner (breeding) production system. Further, years of farming experience, access to extension service, number of initial stocks, and gender significantly influenced the choice of the farrow to finish production system. Significant predictors for the weaner-to-slaughter (fattening) system were market proximity, years of farming experience, household size, number of initial stocks, and access to extension service. It is recommended that extension services be enhanced and tailored to specific production systems, with a focus on breeding management, feeding practices, and marketing strategies to better support pig farmers. Further, investments should be made in transportation infrastructure to facilitate direct farm-to-market linkages for pig farmers.